2017
DOI: 10.18632/oncotarget.19382
|View full text |Cite|
|
Sign up to set email alerts
|

Aliskiren therapy in hypertension and cardiovascular disease: a systematic review and a meta-analysis

Abstract: The efficacy and safety of aliskiren combination therapy with angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) in patients with hypertension and cardiovascular disease remains attractive attention. We searched the Cochrane Central Register, the Clinical Trials Registry, EMBASE, MEDLINE and PubMed for relevant literatures up to January 2017. A total of 13 randomized controlled trials (RCTs) with 12222 patients were included in this study, and the combined results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…ACE inhibitors and ARBs should not be used together and should not be used in combination with direct renin inhibitors (i.e., aliskiren), largely due to questionable added benefits, and potential for hyperkalemia. [161 , 177] Calcium channel blocker (CCBs) may help treat angina and cardiac dysrhythmias; however, dihydropyridine CCBs (e.g., amlodipine, nifedipine) may cause edema and non-dihydropyridine CCBs (e.g., verapamil and diltiazem) may cause bradycardia and heart block and should be avoided in patients with heart failure with reduced left ventricular ejection fraction. CCBs lower blood pressure and are first line antihypertensive agents.…”
Section: High Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…ACE inhibitors and ARBs should not be used together and should not be used in combination with direct renin inhibitors (i.e., aliskiren), largely due to questionable added benefits, and potential for hyperkalemia. [161 , 177] Calcium channel blocker (CCBs) may help treat angina and cardiac dysrhythmias; however, dihydropyridine CCBs (e.g., amlodipine, nifedipine) may cause edema and non-dihydropyridine CCBs (e.g., verapamil and diltiazem) may cause bradycardia and heart block and should be avoided in patients with heart failure with reduced left ventricular ejection fraction. CCBs lower blood pressure and are first line antihypertensive agents.…”
Section: High Blood Pressurementioning
confidence: 99%
“…ACE inhibitors and ARBs should not be used together and should not be used in combination with direct renin inhibitors (i.e., aliskiren), largely due to questionable added benefits, and potential for hyperkalemia. [161 , 177] …”
Section: High Blood Pressurementioning
confidence: 99%
“…A total of 13 randomized controlled trials with 12,222 patients indicated that aliskiren in combination therapy with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers had remarkable effects in reducing both systolic and diastolic blood pressure when compared with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers monotherapy, but with significantly increased risk of hyperkalaemia and kidney injury. Relatively high dose (300 mg/kg/day) of aliskiren was used in the majority of trials [27]. In the animal study using SHR, aliskiren at high (60 mg/kg/day), but not low dose (30 mg/kg/day) prevented age-related increases in blood pressure [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unlike angiotensin-converting enzyme (ACE) inhibitors and Ang II receptor blockers, aliskiren neutralizes any compensatory increase in plasma renin by preventing formation of Ang I and Ang II [ 25 ]. Aliskiren administration not only has a favorable effect on blood pressure (BP) reduction but also acts on target organs damaged by hypertension, preventing or treating, for example, cardiovascular and renal dysfunction [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%